An emerging Platynota sp. (Lepidoptera: Tortricidae) infesting blueberry (Vaccinium corymbosum) in the central coast of Peru - Velasquez, Ricardo; Leiva, Ana Maria; Gil-Ordóñez, Alejandra; Perez-Fuentes, Lady Susan; Domínguez, Viviana; Cuellar, Wilmer J. (Frontiers in Insect Science, 2025)
Blueberry cultivation has recently become a rapidly expanding export industry in Peru. With few to no official records of phytosanitary problems up to date. Nevertheless, as observed in other major blueberry producer countries, pests occurrences have been already reported. This study presents a comprehensive biological and molecular characterization of a novel blueberry pest, identifying it as a member of the Tortricidae family in the genus Platynota. The insect’s average life cycle was determined to be 46.3 days for males and 48.6 days for females, with the larval stage being the longest (25.4 days on average), and the most destructive due to its feeding behavior, which significantly damages buds and fruits. Morphological analysis of the genitalia, along with a comparison of its complete mitochondrial DNA, further supports the conclusion that this pest is a new species. These findings represent the first report of a tortricid pest affecting blueberries in Peru and offer crucial insights for developing effective pest management strategies, contributing to the sustainable growth of blueberry production and exports in the region.